The politics of emergency and the demise of the developing state: problems for humanitarian advocacy - Pupavac, Vanessa (Routledge, 2006)
This article discusses the dilemmas of humanitarian advocacy in the contemporary world. First the article considers the crisis of humanitarianism within the wider crisis of meaning in international politics which encouraged humanitarian advocacy. Humanitarian advocacy in the last fifteen years has drawn attention to how humanitarian crises have been precipitated by state policies and has sought international intervention to protect people. Accordingly humanitarian advocacy has become associated with challenging the national sovereignty of the developing state. However rather than the strong sovereign state lying behind today’s humanitarian crises, the article contends that the weak state is the problem. The article suggests that the existing humanitarian advocacy paradigm risks legitimising further erosion of weak states. Humanitarian advocacy has arguably complimented neoliberal economic policies hollowing out the developing state and abandoning national development. The article concludes that humanitarian advocacy should prioritise reasserting the importance of humanitarian relief without conditionality and how to regain humanitarian access on the basis of consent. A later revised and proofed version of this article was published as follows :- Vanessa Pupavac (2006) ‘The politics of emergency and the demise of the developing state: problems for humanitarian advocacy.’ Development in Practice, Special Issue on Current Issues in International Humanitarianism, Vol. 16, Nos. 3&4, June, 2006, pp. 255-269 (first article in special issue). Article reprinted in Tony Vaux (ed.) Development and Humanitarianism: Some Practical Issues. Bloomfield: Kumarian Press, 2007, pp. 27-49.